Modeling and simulation of the lateral photovoltage scanning method. (15th November 2021) - Farrell, Patricio; Kayser, Stefan; Rotundo, Nella
Abstract: The goal of this paper is to model and simulate the lateral photovoltage scanning (LPS) method which detects inhomogeneities in semiconductor crystals. Our drift-diffusion model is based on the semiconductor device equations combined with an implicit boundary condition which models a volt meter. To validate our 2D and 3D finite volume simulations, we use theory developed by Tauc [1] to derive three analytical predictions which our simulation results corroborate, even for anisotropic 2D and 3D meshes. Our code runs about two orders of magnitudes faster than earlier implementations based on commercial software [2] . It also performs well for small doping concentrations which previously could not be simulated at all due to numerical instabilities. We present a convergence study which shows that the LPS voltage converges quadratically. Finally, our simulations provide experimentalists with reference laser powers for which meaningful voltages can still be measured. For higher laser power the screening effect does not allow this anymore.